Genetics of kidney stones and the role of genetic testing in prevention: a guide for urologists - Pintus, Francesco; Giordano, Noemi; Giachino, Daniela Francesca; Mandrile, Giorgia (Frontiers in Medicine, 2025)
Kidney Stone Disease (KSD) has a high prevalence (approximately 10%) and high recurrence risk: almost half of stone former patients will experience recurrence within 5–10 years. To date, KSD is managed mostly surgically with a heavy burden on the healthcare system and numerous invasive procedures for the patients. In the past years a genetic basis in KSD has been increasingly recognized, with a heritability rate reaching 50%. Through Genome-Wide Association Studies (GWAS) and Next-Generation Sequencing (NGS) several genetic causes of recurrent nephrolithiasis have been untangled, paving the way to new therapies and prevention strategies, through precision medicine-based approaches. Many loci with more than 200 unique genes have been associated with KSD susceptibility thanks to GWAS, even though the development of a polygenic risk score is still in progress. Moreover, today, about 40 genes linked to monogenic disease that are involved in kidney stones have been identified, leading to a precise diagnosis in cases that were previously considered idiopathic. Despite these advancements, genetic testing in kidney stone formers remains underutilized and inconsistently available. The absence of clear diagnostic guidelines, standardization, and widespread awareness, combined with lack of perceived benefit, has left the decision to test largely at the discretion of individual physicians. This paper reviews the updated evidences in KSD genetics and suggest a diagnostic algorithm aimed to increase the diagnostic rate of genetic stones, allowing a personalized treatment and, in turn, a higher disease-free survival for the patients and a more efficient allocation of resources, analyzing the cost-effectiveness of genetic testing in urolithiasis. Besides, it will provide a further look to promising prospects in the field of prevention methods for kidney stones.